2017
DOI: 10.3945/jn.116.239335
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Midpregnancy Plasma trans 18:1 Fatty Acid Concentrations Are Positively Associated with Risk of Maternal Vascular Complications and Child Low Birth Weight

Abstract: Evidence is plentiful that fatty acids (TFAs) induce vascular inflammation with adverse metabolic consequences. However, it is not clear whether TFAs increase the risk of vascular pregnancy complications such as preeclampsia. We investigated associations between midpregnancy maternal plasma 18:1 fatty acid (t18:1) concentrations and pregnancy course and outcomes. Participants were 6695 pregnant women and newborns from the Generation R Study, Rotterdam, Netherlands (enrollment in 2001-2005). Maternal midpregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…DHA levels ranged from 3.34 to 5.76% and EPA levels ranged from 0.50 to 0.77%. Four studies investigated TFAs and birth weight (32,33,77,79). Three studies found that high levels of TFAs during pregnancy were related to a lower weight at birth (33,77,79), while one study found no association between TFAs and birth weight (32) Two studies calculated regression coefficients and showed the relation between maternal levels of different fatty acids and birth weight (76,78).…”
Section: Results From the Observational Studies Birth Weightmentioning
confidence: 99%
See 4 more Smart Citations
“…DHA levels ranged from 3.34 to 5.76% and EPA levels ranged from 0.50 to 0.77%. Four studies investigated TFAs and birth weight (32,33,77,79). Three studies found that high levels of TFAs during pregnancy were related to a lower weight at birth (33,77,79), while one study found no association between TFAs and birth weight (32) Two studies calculated regression coefficients and showed the relation between maternal levels of different fatty acids and birth weight (76,78).…”
Section: Results From the Observational Studies Birth Weightmentioning
confidence: 99%
“…In our protocol, we included children up to 18 years of age, but only one observational study investigated the effect of PUFAs on BMI up to 23 years of age (72). In total, 14 eligible observational studies investigated the relationship between blood levels of TFAs or n-3 LCPUFA during pregnancy or from cord blood or placental tissues, in relation to birth weight or weight in childhood (32,33,(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82). All the included observational studies are summarized in Table 4.…”
Section: Description Of Studies and Participantsmentioning
confidence: 99%
See 3 more Smart Citations